The Incremental Prognostic Value of the Clinical Residual SYNTAX Score for Patients With Chronic Renal Insufficiency Undergoing Percutaneous Coronary Intervention - Yan, Liqiu; Li, Peiyao; Wang, Yabin; Han, Dong; Li, Sulei; Jiang, Min; Cao, Xufen; Cao, Feng (Frontiers in Cardiovascular Medicine, 2021)
Background: The residual SYNTAX score (rSS) is considered a powerful prognostic indicator for determining a reasonable revascularization strategy in patients undergoing percutaneous coronary intervention (PCI), but the absence of clinical parameters is one of the limitations of rSS, especially in the chronic renal insufficiency (CRI) comorbidity setting. The present work aimed to investigate the incremental prognostic value of clinical residual SYNTAX score (CrSS) compared with rSS in CRI cases after PCI. Methods: Totally 2468 consecutive CRI cases who underwent PCI from January 2014 to September 2017 were included in this retrospective analysis. CrSS was obtained by multiplying rSS by the modified ACEF score. Individuals with CrSS>0 were considered to have incomplete revascularization and stratified by CrSS tertiles, the remaining cases constituted the complete revascularization (CR) group. The outcomes between these groups were compared. Results: At a median follow-up of 3 years, compared with CR group, individuals with CrSS>12 showed elevated rates of all clinical outcomes, and those with CrSS≤12 showed similar all-cause and cardiac mortality rates. In multivariable analysis, CrSS was a powerful independent predictive factor of all clinical outcomes. The net reclassification improvement levels of CrSS over rSS for all-cause and cardiac mortality rates were 10.3% (p=0.007) and 16.4% (p<0.001), respectively. Compared with rSS, CrSS markedly ameliorated all-cause and cardiac mortality risk stratification. Conclusions: Compared with rSS, CrSS has incremental predictability for long-term all-cause and cardiac mortality in CRI cases following PCI. Keywords: residual SYNTAX score, clinical residual SYNTAX score, coronary artery disease, percutaneous coronary intervention, chronic renal insufficiency